The Language of Engagement: Analysing New Media Terms in The Context of Digital Activism - Imam Jahrudin Priyanto; Arif Husein Lubis; Desayu Eka Surya (UPT Publikasi Ilmiah UNISBA, 2026)
Digital activism represents the development of political communication mediated by new media, which enable the reconstruction of identity, the escalation of mobilisation, and civic participation. In the Indonesian context, an inquiry into the ever-evolving forms of digital communication is crucial yet remains underexplored in the literature on how it engages public attention. This study investigates how evaluative labels of digital activism—such as hashtag activism, slacktivism, and clicktivism—shape perceptions of legitimacy and patterns of online engagement. It addresses gaps in existing literature by providing cross-platform and non-Western evidence from Indonesia. A mixed-methods design was employed, combining quantitative content analysis of 10,000 Indonesia-anchored posts (Twitter (X), Facebook, Instagram, blogs; 2015–2023) with qualitative critical discourse analysis. Posts were coded for framing valence, actor type, and engagement outcomes. Inter-coder reliability was established (Cohen’s κ=0.85). Logistic regression tested the predictive effects of terminology on engagement, while Fairclough’s CDA framework contextualised discursive practices. Positive framings (e.g., hashtag activism) significantly increased the likelihood of active engagement. In contrast, negative labels (e.g., slacktivism) were associated with lower participation and were frequently employed by mainstream media and institutional actors to delegitimise grassroots mobilisation. Platform visibility moderated these relationships, with trending indicators amplifying the effects of framing.